Analysis of the Differences in Supreme Court Rulings in Tax Case Review: Implications for Legal Consistency (Study of Supreme Court Decisions Number 4421/B/PK/PJK/2023 and Number 5201/B/PK/PJK/2023) - Erlangga, Rully; Albab, Ulil (Law and Justice, 2024)
This study aims to explore the decision-making process in the Supreme Court and its impact on legal consistency through a normative approach and document analysis. The research focuses on Supreme Court Decision Number 4421/B/PK/Pjk/2023 regarding the Judicial Review of Tax Court Decision Number 000953.16/2022/PP/M.VB in 2022, which granted the Judicial Review request, as well as Supreme Court Decision Number 5201/B/PK/Pjk/2023 regarding the Judicial Review of Tax Court Decision Number 00957.16/2022/PP/M.VB in 2022, which denied the Judicial Review request. Although the subject matter of the disputes was the same, specifically the determination of Value Added Tax (VAT) obligations for the 2016 tax year, the rulings were different. This research adopts a normative approach that examines the applicable legal norms and principles, along with document analysis to evaluate the Supreme Court decisions. The study identifies the factors influencing judicial interpretation and the complexity of achieving legal consistency within the judicial system through an in-depth analysis of the decision texts and legal considerations. The research aims to provide insight into legal consistency, the factors causing differences in rulings, and the decision-making process within the Supreme Court. Additionally, the study highlights the implications for legal stability and public trust while offering critiques and recommendations for improving legal policy and practice in the future. Overall, this research serves to deepen the understanding of the dynamics of court decisions at the highest level and contributes to enhancing the legal system to be more consistent and just.